A educação como fator de equidade em questões étnico-raciais e de gênero no Brasil - de Almeida, Jémerson Quirino; Lofego, Silvio Luiz; de Castro, Alexandre (Faculdade de Filosofia e Ciências, 2020)
This article aims to present some questions about the relationship between public policies and education in confronting multiple forms of discrimination and prejudice, particularly in terms of gender and race in Brazilian society. Breathing airs of relative democracy in the 1980-1990 decade, Brazil and the world allowed themselves openness processes, culminating in the collapse of some walls, contesting injustices, even correcting certain inequalities. Therefore, starting from legal issues, we established a dialogue with important theoretical references on gender and race themes, such as: Francisco Bethencourt (2018); Nilma Gomes (2008); Fúlvia Rosemberg (2018); Nancy Fraser (2009), reflecting on affirmative actions, policies to combat inequality and the oppression of minorities, highlighting struggles and changes that have occurred in the long term. It is estimated that the reflection proposed here has the power to make us rethink ourselves in the face of our Eurocentric colonial formation, and we can increasingly assume our multicultural characteristics. Unlike the proposal for social harmony, miscegenation or racial democracy, the multicultural perspective would assume the conflicts and asymmetries of power present at the time of national cultural formation.